PENERAPAN MODEL NUMBERED HEAT TOGETHER BERBANTUAN MEDIA HANDOUT DILENGKAPI LKPD TTS UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK SMP MUHAMMADIYAH WAINGAPU - Day Tara, Resi; Makaborang, Yohana; Meissy Matulessy, Yoin (Universitas Cokroaminoto Palopo, 2025)
The purpose of this study was to describe the cognitive and affective learning outcomes of students and the improvement of learning outcomes of SMP Muhammadiyah Waingapu implementing the Numbered Head Together model assisted by handout media equipped with LKPD TTS. This study is a Classroom Action Research (CAR) using a descriptive quantitative approach. The subjects in this study were students of class VIII A of SMP Muhammadiyah Waingapu. The data collection instruments used consisted of observation sheets and written tests. The results of this study showed a significant increase in cognitive learning outcomes, from 31% in the pre-cycle increasing to 75% in cycle I, and then increasing again to 94% in cycle II. Therefore, it can be concluded that the application of the numbered head together model assisted by handout media equipped with LKPD TTS can improve the learning outcomes of students of class VIII A of SMP Muhammadiyah Wangapu.